Let $ a_n$ be a sequence, so that $ \sum_{i = 1}^\infty a_n$ converges and $ a_k \ge 0 \forall k \in \mathbb{N} $

I want to prove the following property of convergent series:

$ \forall \epsilon \gt 0 \exists n_0 \in \mathbb{N} $ so that $ \sum_{i = n_0}^\infty <\epsilon $

However I think my proof is not very elegant (because I have probably overlooked something) and I think/hope there is a better way to show this.

(sketch of the proof)

Proof by contradiction: Now $ \exists \epsilon > 0 : \forall n_0 \in \mathbb{N} $ either $ \exists n_m \in \mathbb{N} $ so that: $ \sum_{i = n_0}^{n_m} > \epsilon $ (Case 1)

or $ \sum_{i = n_0}^{\infty} = \epsilon $ (Case 2)

Case 1 can be brought to contradiction, because $ \sum_{i = 1}^\infty a_n$ converges, while the series in Case 1 tends to infinity.

In case 2, there is obviously a $a_m \ne 0 $ for some m. Setting $a_0 = a_{m+1} $ gets one to: $ \sum_{i = n_0}^{\infty} = \epsilon - a_m < \epsilon $, which brings one to the wanted contradiction.

In my opinion even this sketch is far too long for such a simple or fundamental property of such a convergent series. Writing everything down clearly would extend the proof even further, thus I hope someone can show me a better/more elegant way to proof this. If there are mistakes in it, I will correct them as soon as possible. (Thx in advance)


I think proving this by contradiction is unnecessary, as it follows almost immediately by definition. Let $(s_n)$ be the sequence of partial sums. Then since $a_k\geq0$, $(s_n)$ is increasing. Hence if the limit is $s$ then $$\sum_{i=n}^\infty a_i=s-s_{n-1}=|s-s_{n-1}|$$ so your result follows by definition of a limit.

  • $\begingroup$ Yes, it is unnecessary. I didn't notice that.. $\endgroup$ – Imago Feb 7 '15 at 15:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.